Flame-retardant waterproof asphalt coiled material and preparation method thereof
Through the multi-layer structure of flame-retardant waterproof asphalt rolls, combined with modified asphalt, polyvinyl chloride and other materials, the problem of easy damage to traditional rolls during long-term use is solved, and efficient waterproof, flame-retardant and heat-insulating properties are achieved. Extends service life and improves building safety and weather resistance.
Patent Information
- Application Number
- CN202411295324.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Traditional waterproof asphalt coils are susceptible to ultraviolet rays, oxidation and mechanical damage during long-term use, and lack of flame retardant and heat insulation performance, resulting in limited application range and service life, and poor fire resistance, making it difficult to meet the high durability of modern buildings. The demand for multifunctional waterproof materials.
Flame-retardant and waterproof asphalt coils with multi-layer structures include upper surface protective layer, waterproof reinforcement layer, fire-proof insulation layer and lower surface protective layer, respectively, modified asphalt, polyvinyl chloride, antioxidant, nano-alumina, and hydrogen Magnesium oxide, foamed polyurethane, glass fiber and other materials are formed through composite processes. Self-healing materials and nanotitanium dioxide are used to improve weather resistance and self-cleaning properties.
It achieves good flame retardant performance, reduces flame spreading speed, improves building safety, excellent waterproof performance, prevents moisture penetration, extends service life, reduces maintenance needs, improves weather resistance and flame retardant performance, and is suitable for a variety of building applications.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of waterproof coiled materials, and in particular to a flame retardant waterproof asphalt coiled material and a preparation method thereof. Background Art
[0002] As the construction industry continues to increase its requirements for the performance of building materials, waterproof, flame retardant and thermal insulation properties have become crucial indicators in building materials. In multi-story building structures, waterproof asphalt membranes are widely used in roofs, basements and other parts exposed to environmental factors to ensure the durability and safety of buildings. In order to improve the comprehensive performance of waterproof membranes, especially to enhance their flame retardant, thermal insulation and protective properties, researchers are constantly exploring new material formulas and preparation processes.
[0003] Although traditional waterproof asphalt membranes have good waterproof properties, they have certain deficiencies in flame retardancy and heat insulation. In addition, conventional materials are easily affected by ultraviolet rays, oxidation and mechanical damage during long-term use, which limits their scope of application and service life. Moreover, although common asphalt membranes have good waterproof properties, their fire resistance is poor and they are easy to burn in high temperature environments. In addition, ordinary asphalt membranes are prone to aging and cracking during long-term use, and it is difficult to meet the needs of modern buildings for highly durable and multifunctional waterproof materials. In order to improve the comprehensive performance of waterproof materials for buildings, composite materials have gradually become a research hotspot. Therefore, the development of a new type of flame-retardant waterproof asphalt membrane is an important research direction in the current field of materials science and engineering technology. Summary of the invention
[0004] In view of this, the present invention proposes a flame retardant waterproof asphalt roll and a preparation method thereof, aiming to solve the problem in the current technology that conventional materials are easily affected by ultraviolet rays, oxidation and mechanical damage during long-term use, which limits their application scope and service life.
[0005] On the one hand, the present invention provides a flame retardant waterproof asphalt roll material, which includes the following layers from top to bottom: The upper surface protective layer comprises the following components in parts by weight: 30-35 parts of modified asphalt, 15-20 parts of polyvinyl chloride, 1-2 parts of antioxidant, 0.5-1.0 parts of ultraviolet stabilizer, 3-5 parts of nano-alumina, 2 parts of nano-titanium dioxide, 10-15 parts of magnesium hydroxide and 1-1.5 parts of self-healing material; The waterproof reinforcement layer comprises the following components in parts by weight: 25 parts of modified asphalt, 25 parts of polyvinyl chloride, 12-15 parts of polyester fiber, 2-3 parts of low molecular weight polyethylene, 3-4 parts of toughening agent and 2-3 parts of plasticizer; The fireproof and heat-insulating layer comprises the following components in parts by weight: 35-45 parts of foamed polyurethane, 20-25 parts of expanded perlite, 10-15 parts of glass fiber, 0.5-1 parts of magnesium carbonate and 5-10 parts of hollow glass microspheres; The lower surface protective layer comprises the following components in parts by weight: 30-35 parts of polytetrafluoroethylene, 20-25 parts of ethylene-tetrafluoroethylene copolymer, 8-12 parts of aramid fiber and 5-10 parts of plasticizer; The self-healing material is a microcapsule containing 4-6% by mass of dicyanoacrylate, 3-5% by mass of trimellitic anhydride and 1-2% by mass of diisocyanate.
[0006] Optionally, the antioxidant comprises 10-15% by volume of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 20-25% of dioctyl thiodipropionate, 10-15% of tris[2,4-di-tert-butylphenyl]phosphite, and the remainder of toluene and impurities; The ultraviolet stabilizer is 0.3-0.7 parts by weight of UV-1164 and 0.2-0.5 parts by weight of UV-360; The particle size of the magnesium hydroxide is 1-2 μm.
[0007] Optionally, the molecular weight of the low molecular weight polyethylene is 1000-5000; the toughening agent is ethylene-propylene-diene monomer; and the plasticizer is dioctyl phthalate.
[0008] Optionally, the compression strength of the foamed polyurethane is 0.3-0.5 MPa; the particle size of the expanded perlite is 50-100 μm; the particle size of the hollow glass microspheres is 40-120 μm, and the aramid fiber is poly(p-phenylene terephthalamide) fiber.
[0009] Optionally, the particle size of the microcapsules is in the range of 50-100 μm.
[0010] On the other hand, the present invention also proposes a method for applying the above-mentioned flame retardant and waterproof asphalt membrane, the method comprising the following steps: Separately preparing an upper surface protective layer, a waterproof reinforcement layer, a fireproof and heat-insulating layer, and a lower surface protective layer; The upper surface protection layer, the waterproof reinforcement layer, the fireproof and heat-insulating layer and the lower surface protection layer are compounded after controlling the temperature, and after the compounding is completed, they are cooled and solidified for 30 minutes.
[0011] Optionally, the preparation method of the upper surface protective layer is: The modified asphalt and polyvinyl chloride are mixed and stirred at 160-180°C to form a uniform molten mixture; Adding antioxidant, UV stabilizer, nano-alumina, nano-titanium dioxide and magnesium hydroxide to the molten mixture in sequence, and continuing to stir until completely uniform; The self-healing material is slowly added in the form of microcapsules, and stirring is continued until the molten mixture is evenly dispersed, and then the molten mixture is coated on the surface of the waterproof reinforcement layer to form an upper surface protective layer.
[0012] Optionally, the preparation method of the fireproof and heat-insulating layer is: Premixing the foamed polyurethane and the expanded perlite at 60-80°C for 30-45 minutes to form a mixture; Adding the surface-treated glass fibers and hollow glass microspheres into the mixture in sequence, and continuing to mix until uniform; The mixture is heat-pressed at 100-120° C. to form a fireproof and heat-insulating layer.
[0013] Optionally, the preparation method of the lower surface protective layer is: The polytetrafluoroethylene and ethylene-tetrafluoroethylene copolymer are melt-mixed at 200-220° C. and homogenized by high-speed shear stirring to obtain a homogenized mixture; Evenly adding aramid fibers in a certain proportion into the homogenized mixture, and continuing stirring; After the homogenized mixture is cooled to room temperature, a plasticizer is added, and a degassing treatment is performed under vacuum conditions, and then the mixture is coated on the lower surface of the fireproof and heat-insulating layer to form a lower surface protective layer; The preparation method of the waterproof reinforcement layer is: The modified asphalt and polyvinyl chloride are melted and mixed at 150-180°C and homogenized by high-speed shear stirring; Gradually add low molecular weight polyethylene, toughening agent and plasticizer, and continue stirring until uniform; evenly disperse polyester fiber into the homogenized mixture according to proportion, and continue stirring; The mixture is extruded and cooled to form a waterproof reinforcement layer.
[0014] Optionally, the upper surface protective layer is cured for 40 minutes at 70-90°C after coating, the waterproof reinforcement layer is cured for 50 minutes at above 50°C, the fireproof and heat-insulating layer is hot-pressed at 100°C and then cooled to 20°C, and cured for 90 minutes at 20°C, and the lower surface protective layer is cured for 50 minutes at 20°C after coating.
[0015] Compared with the prior art, the beneficial effect of the present invention is that the flame retardant and waterproof asphalt coiled material provided by the present invention has good flame retardant properties, can effectively reduce the flame spread speed when a fire occurs, and improve the safety of the building. Moreover, the coiled material has excellent waterproof performance, can effectively prevent moisture penetration, and ensure the dry environment of the building. The upper surface protective layer prepared by the self-healing material can achieve self-healing when microcracks appear on the surface of the coiled material, thereby extending the service life of the coiled material. The nano titanium dioxide in the upper surface protective layer can also be self-cleaned, reduce the accumulation of surface dirt, and reduce maintenance requirements. The addition of antioxidants and ultraviolet stabilizers improves the weather resistance of the coiled material, so that it can still maintain good performance in harsh environments. The setting of the fireproof and heat-insulating layer further improves the flame retardant properties of the coiled material and reduces the risk of fire. The polytetrafluoroethylene and ethylene-tetrafluoroethylene copolymer of the lower surface protective layer have good chemical stability, can effectively prevent the coiled material from aging, and improve the service life. The preparation method is simple, the production efficiency is high, and it is convenient for large-scale production. The coiled material of the present invention is suitable for waterproofing and fire prevention projects such as roofs, basements, and toilets of various buildings, and has a high market application value. DETAILED DESCRIPTION
[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] This embodiment provides a flame retardant waterproof asphalt coiled material, which includes the following layers from top to bottom: The upper surface protective layer comprises the following components in parts by weight: 30-35 parts of modified asphalt, 15-20 parts of polyvinyl chloride, 1-2 parts of antioxidant, 0.5-1.0 parts of ultraviolet stabilizer, 3-5 parts of nano-alumina, 2 parts of nano-titanium dioxide, 10-15 parts of magnesium hydroxide and 1-1.5 parts of self-healing material; The waterproof reinforcement layer comprises the following components in parts by weight: 25 parts of modified asphalt, 25 parts of polyvinyl chloride, 12-15 parts of polyester fiber, 2-3 parts of low molecular weight polyethylene, 3-4 parts of toughening agent and 2-3 parts of plasticizer; The fireproof and heat-insulating layer comprises the following components in parts by weight: 35-45 parts of foamed polyurethane, 20-25 parts of expanded perlite, 10-15 parts of glass fiber, 0.5-1 parts of magnesium carbonate and 5-10 parts of hollow glass microspheres; The lower surface protective layer comprises the following components in parts by weight: 30-35 parts of polytetrafluoroethylene, 20-25 parts of ethylene-tetrafluoroethylene copolymer, 8-12 parts of aramid fiber and 5-10 parts of plasticizer; The self-healing material is a microcapsule containing 4-6% by mass of dicyanoacrylate, 3-5% by mass of trimellitic anhydride and 1-2% by mass of diisocyanate.
[0018] Optionally, the antioxidant comprises 10-15% by volume of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 20-25% of dioctyl thiodipropionate, 10-15% of tris[2,4-di-tert-butylphenyl]phosphite, and the remainder of toluene and impurities; The ultraviolet stabilizer is 0.3-0.7 parts by weight of UV-1164 and 0.2-0.5 parts by weight of UV-360; The particle size of the magnesium hydroxide is 1-2 μm.
[0019] Optionally, the molecular weight of the low molecular weight polyethylene is 1000-5000; the toughening agent is ethylene-propylene-diene monomer; and the plasticizer is dioctyl phthalate.
[0020] Optionally, the compression strength of the foamed polyurethane is 0.3-0.5 MPa; the particle size of the expanded perlite is 50-100 μm; the particle size of the hollow glass microspheres is 40-120 μm, and the aramid fiber is poly(p-phenylene terephthalamide) fiber.
[0021] Optionally, the particle size of the microcapsules is in the range of 50-100 μm.
[0022] It is understood that modified asphalt and polyvinyl chloride work together in the upper surface protection layer and waterproof reinforcement layer to provide excellent waterproof performance, ensuring that the material can maintain its waterproof effect in all weather conditions. Fire retardant materials such as magnesium hydroxide, nano-alumina, magnesium carbonate and glass fiber are used in each layer to significantly improve the fire resistance of the material and meet high standards of fire protection requirements. The self-healing material in the upper surface protection layer can automatically repair cracks when the material is damaged, extend the service life of the material and reduce maintenance costs. The foamed polyurethane, expanded perlite and hollow glass microspheres in the fireproof and thermal insulation layer work together to provide excellent thermal insulation performance and improve the energy efficiency of the building. Polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer and aramid fiber in the lower surface protection layer provide excellent chemical corrosion resistance and mechanical protection, ensuring that the material can still maintain its function in harsh environments. Nano-titanium dioxide in the upper surface protection layer can also self-clean, reduce the accumulation of surface dirt and reduce maintenance requirements.
[0023] The embodiment of the present invention also provides a method for preparing a flame retardant and waterproof asphalt coiled material, comprising the following steps: Separately preparing an upper surface protective layer, a waterproof reinforcement layer, a fireproof and heat-insulating layer, and a lower surface protective layer; The upper surface protection layer, the waterproof reinforcement layer, the fireproof and heat-insulating layer and the lower surface protection layer are compounded after controlling the temperature, and after the compounding is completed, they are cooled and solidified for 30 minutes.
[0024] Optionally, the preparation method of the upper surface protective layer is: The modified asphalt and polyvinyl chloride are mixed and stirred at 160-180°C to form a uniform molten mixture; Adding antioxidant, UV stabilizer, nano-alumina, nano-titanium dioxide and magnesium hydroxide to the molten mixture in sequence, and continuing to stir until completely uniform; The self-healing material is slowly added in the form of microcapsules, and stirring is continued until the molten mixture is evenly dispersed, and then the molten mixture is coated on the surface of the waterproof reinforcement layer to form an upper surface protective layer.
[0025] Optionally, the preparation method of the fireproof and heat-insulating layer is: Premixing the foamed polyurethane and the expanded perlite at 60-80°C for 30-45 minutes to form a mixture; Adding the surface-treated glass fibers and hollow glass microspheres into the mixture in sequence, and continuing to mix until uniform; The mixture is heat-pressed at 100-120° C. to form a fireproof and heat-insulating layer.
[0026] Optionally, the preparation method of the lower surface protective layer is: The polytetrafluoroethylene and ethylene-tetrafluoroethylene copolymer are melt-mixed at 200-220° C. and homogenized by high-speed shear stirring to obtain a homogenized mixture; Evenly adding aramid fibers in a certain proportion into the homogenized mixture, and continuing stirring; After the homogenized mixture is cooled to room temperature, a plasticizer is added, and a degassing treatment is performed under vacuum conditions, and then the mixture is coated on the lower surface of the fireproof and heat-insulating layer to form a lower surface protective layer; The preparation method of the waterproof reinforcement layer is: The modified asphalt and polyvinyl chloride are melted and mixed at 150-180°C and homogenized by high-speed shear stirring; Gradually add low molecular weight polyethylene, toughening agent and plasticizer, and continue stirring until uniform; evenly disperse polyester fiber into the homogenized mixture according to proportion, and continue stirring; The mixture is extruded and cooled to form a waterproof reinforcement layer.
[0027] Optionally, the upper surface protective layer is cured for 40 minutes at 70-90°C after coating, the waterproof reinforcement layer is cured for 50 minutes at above 50°C, the fireproof and heat-insulating layer is hot-pressed at 100°C and then cooled to 20°C, and cured for 90 minutes at 20°C, and the lower surface protective layer is cured for 50 minutes at 20°C after coating.
[0028] In this way, the materials are usually added or sprayed layer by layer, which allows the thickness, composition and order of each layer to be flexibly adjusted, facilitating customized production. In addition, this method allows the use of materials that are unstable or cannot be melted under high temperature and pressure, expanding the range of material choices. Layer-by-layer lamination can also be carried out under low temperature conditions to avoid the performance degradation of certain materials at high temperatures.
[0029] Furthermore, the preparation method can also use a co-extrusion process for compounding, and the specific steps are: 1. Material Preparation Before optimizing the coextrusion lamination method, the materials for each layer must first be prepared in detail: Upper surface protective layer: modified asphalt, polyvinyl chloride, antioxidants, UV stabilizers, nano-alumina, magnesium hydroxide and self-healing materials.
[0030] Waterproof reinforcement layer: modified asphalt, polyvinyl chloride, polyester fiber, low molecular weight polyethylene, toughening agent and plasticizer.
[0031] Fireproof insulation layer: foamed polyurethane, expanded perlite, glass fiber, magnesium carbonate and hollow glass microspheres.
[0032] Lower surface protective layer: polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, aramid fiber and plasticizer.
[0033] 2. Preprocessing Upper surface protective layer: Mix and stir the modified asphalt and polyvinyl chloride at 160-180°C to form a uniform molten mixture, add antioxidant, UV stabilizer, nano-alumina, nano-titanium dioxide and magnesium hydroxide in sequence, continue stirring until uniform, slowly add self-healing material in the form of microcapsules and stir evenly.
[0034] Waterproof reinforcement layer: melt and mix the modified asphalt and polyvinyl chloride at 150-180°C, perform homogenization treatment, gradually add low molecular weight polyethylene, toughening agent and plasticizer, stir until uniform, evenly disperse the polyester fiber in the mixture, and continue stirring.
[0035] Fireproof and heat-insulating layer: Premix foamed polyurethane and expanded perlite at 60-80°C, mix for 30-45 minutes, add surface-treated glass fiber and hollow glass microspheres, continue mixing until uniform, and perform hot pressing at 100-120°C to form a fireproof and heat-insulating layer.
[0036] Lower surface protective layer: melt and mix polytetrafluoroethylene and ethylene-tetrafluoroethylene copolymer at 200-220°C, perform homogenization, add aramid fiber into the homogenized mixture, stir evenly, cool to room temperature, add plasticizer, and perform vacuum degassing for standby use.
[0037] 3. Co-extrusion compounding Temperature control between layers: upper surface protection layer: maintain at 70-90℃ for 40 minutes; waterproof reinforcement layer: maintain at above 50℃ for 50 minutes; fireproof and heat-insulating layer: cool to 20℃ after hot pressing at 100℃, and cure at 20℃ for 90 minutes; lower surface protection layer: cure at 20℃ for 50 minutes.
[0038] Co-extrusion process: Use multi-layer co-extrusion equipment to compound each layer of materials in sequence. Ensure that each layer of material maintains appropriate fluidity and temperature during the extrusion process to ensure good adhesion between layers. The composite material is cooled as a whole. The cooling time and temperature should be adjusted according to the characteristics of each layer of material and equipment requirements to ensure the bonding strength between the layers.
[0039] Cooling and curing: After the co-extrusion lamination is completed, the entire coil needs to pass through the cooling area to ensure that the temperature gradually drops to room temperature. The cooling time should ensure that each layer of the coil is evenly cured to avoid interlayer delamination or performance degradation due to uneven cooling.
[0040] In this way, the above four layers of materials can be manufactured by co-extrusion compounding to form a multi-layer structure in one processing process, which significantly improves production efficiency and reduces production steps and time. In this way, the production process is more efficient and reduces production costs. Co-extrusion compounding technology can form good adhesion between the layers of materials to ensure that the layers of materials can be tightly combined. This close combination not only improves the overall strength and durability of the coil, but also avoids the occurrence of delamination. Co-extrusion compounding technology allows the thickness of each layer of material to be precisely controlled to ensure that the thickness of each layer meets the design requirements. This precise control helps to optimize the performance of the material so that each layer of material can perform its best function. Through co-extrusion compounding, each layer of material can be evenly distributed in the coil to ensure that the various properties of the material are uniform. In this way, the waterproof, fireproof, heat-insulating, self-healing and other properties of the entire coil can be optimized and evenly distributed, improving the overall performance.
[0041] The performance of the flame retardant and waterproof asphalt coiled material prepared by the present invention is described in detail by way of examples below: Example 1
[0042] Upper surface protective layer: modified asphalt: 32 parts by weight, polyvinyl chloride: 18 parts by weight, antioxidant: 1.5 parts by weight, ultraviolet stabilizer: 0.8 parts by weight, nano alumina: 4 parts by weight, nano titanium dioxide: 2 parts by weight, magnesium hydroxide: 12 parts by weight, self-healing material: 1.2 parts by weight; The modified asphalt and polyvinyl chloride are mixed and stirred at 160-180°C to form a uniform molten mixture; an antioxidant, a UV stabilizer, nano-alumina and magnesium hydroxide are sequentially added to the molten mixture, and stirring is continued until it is completely uniform; the self-healing material is slowly added in the form of microcapsules, and stirring is continued until the molten mixture is uniformly dispersed, and the molten mixture is coated on the surface of the waterproof reinforcement layer to form an upper surface protective layer.
[0043] Waterproof reinforcement layer: modified asphalt: 25 parts by weight, polyvinyl chloride: 25 parts by weight, polyester fiber: 14 parts by weight, low molecular weight polyethylene: 2.5 parts by weight, toughening agent: 3.5 parts by weight, plasticizer: 2.5 parts by weight; The modified asphalt and polyvinyl chloride are melted and mixed at 150-180°C, and homogenized by high-speed shear stirring; low molecular weight polyethylene, toughening agent and plasticizer are gradually added, and stirring is continued until uniform; polyester fiber is evenly dispersed in the homogenized mixture according to proportion, and stirring is continued; the mixture is extruded and cooled to form a waterproof reinforcement layer.
[0044] Fireproof and heat-insulating layer: foamed polyurethane: 40 parts by weight, expanded perlite: 23 parts by weight, glass fiber: 12 parts by weight, magnesium carbonate: 0.8 parts by weight, hollow glass microspheres: 7 parts by weight; The foamed polyurethane and the expanded perlite are premixed at 60-80°C for 30-45 minutes to form a mixture; the surface-treated glass fibers and hollow glass microspheres are sequentially added to the mixture and the mixture is continuously mixed until uniform; the mixture is hot-pressed at 100-120°C to form a fireproof and heat-insulating layer.
[0045] Lower surface protective layer: polytetrafluoroethylene: 32 parts by weight, ethylene-tetrafluoroethylene copolymer: 22 parts by weight, aramid fiber: 10 parts by weight, plasticizer: 7 parts by weight; The polytetrafluoroethylene and ethylene-tetrafluoroethylene copolymer are melt-mixed at 200-220° C., and homogenized by high-speed shear stirring to obtain a homogenized mixture; the aramid fiber is evenly added to the homogenized mixture in a certain proportion, and the stirring is continued; after the homogenized mixture is cooled to room temperature, a plasticizer is added, and a degassing treatment is performed under vacuum conditions, and then the mixture is coated on the lower surface of the fireproof and heat-insulating layer to form a lower surface protective layer; The upper surface protection layer, the waterproof reinforcement layer, the fireproof and heat-insulating layer and the lower surface protection layer are compounded after controlling the temperature, and after the compounding is completed, they are cooled and solidified for 30 minutes. Example 2
[0046] Material composition Upper surface protective layer: modified asphalt: 35 parts by weight, polyvinyl chloride: 19 parts by weight, antioxidant: 1.8 parts by weight, ultraviolet stabilizer: 0.9 parts by weight, nano alumina: 5 parts by weight, nano titanium dioxide: 2 parts by weight, magnesium hydroxide: 15 parts by weight, self-healing material: 1.3 parts by weight; Waterproof reinforcement layer: modified asphalt: 25 parts by weight, polyvinyl chloride: 25 parts by weight, polyester fiber: 15 parts by weight, low molecular weight polyethylene: 3 parts by weight, toughening agent: 4 parts by weight, plasticizer: 3 parts by weight; Fireproof and heat-insulating layer: foamed polyurethane: 45 parts by weight, expanded perlite: 25 parts by weight, glass fiber: 15 parts by weight, magnesium carbonate: 1 part by weight, hollow glass microspheres: 10 parts by weight; Lower surface protective layer: polytetrafluoroethylene: 35 parts by weight, ethylene-tetrafluoroethylene copolymer: 25 parts by weight, aramid fiber: 12 parts by weight, plasticizer: 10 parts by weight; The preparation method is the same as that in Example 1. Example 3
[0047] Material composition: Upper surface protective layer: modified asphalt: 30 parts by weight, polyvinyl chloride: 17 parts by weight, antioxidant: 1.5 parts by weight, ultraviolet stabilizer: 0.6 parts by weight, nano-alumina: 3 parts by weight, nano-titanium dioxide: 2 parts by weight, magnesium hydroxide: 10 parts by weight, self-healing material: 1.1 parts by weight; Waterproof reinforcement layer: modified asphalt: 25 parts by weight, polyvinyl chloride: 25 parts by weight, polyester fiber: 12 parts by weight, low molecular weight polyethylene: 2 parts by weight, toughening agent: 3 parts by weight, plasticizer: 2 parts by weight; Fireproof and heat-insulating layer: foamed polyurethane: 35 parts by weight, expanded perlite: 20 parts by weight, glass fiber: 10 parts by weight, magnesium carbonate: 0.5 parts by weight, hollow glass microspheres: 5 parts by weight; Lower surface protective layer: polytetrafluoroethylene: 30 parts by weight, ethylene-tetrafluoroethylene copolymer: 20 parts by weight, aramid fiber: 8 parts by weight, plasticizer: 5 parts by weight; Preparation method: Material preparation: The raw materials such as modified asphalt, polyvinyl chloride, polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, self-healing material, foamed polyurethane, expanded perlite, etc. used for each layer are pre-treated according to the above formula, including drying, mixing and surface treatment.
[0048] Co-extrusion compounding: Use a multi-layer co-extruder to send each layer of pre-treated material into an independent extruder for heating and melting. The molten materials are merged through a co-extrusion die to form a multi-layer flame-retardant and waterproof asphalt membrane. The extrusion temperature is controlled within the range of 150-200°C to ensure that each layer of material is melted and fused at the optimal temperature.
[0049] Cooling and curing: The extruded composite coil is quickly cooled by the cooling system, and the temperature is controlled at 10-25°C to ensure that each layer of material is fully cured and tightly bonded.
[0050] Comparative Example 1 Material composition: Single material waterproof membrane (traditional asphalt membrane) Modified asphalt: 100 parts by weight The modified asphalt is melted at 150-170°C, then extruded and cooled to form a traditional single-material waterproof membrane.
[0051] Comparative Example 2 Material composition: Modified asphalt roll (with added antioxidant and UV stabilizer) Modified asphalt: 95 parts by weight, antioxidant: 2.5 parts by weight, UV stabilizer: 2.5 parts by weight.
[0052] The modified asphalt is melted at 150-170°C, and antioxidants and UV stabilizers are added and mixed uniformly, and then extruded and cooled to form a modified asphalt roll.
[0053] The asphalt membranes prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests. The test data are shown in Table 1, wherein the fire resistance was tested according to GB / T 8624-2012, the waterproof standard was tested according to GB / T 328.10-2007, and the self-healing performance was recorded by scratch test and microscopic observation.
[0054] Table 1 Test data table
[0055] Through the detailed comparison data of the experimental group and the control group, it can be clearly seen that the flame-retardant waterproof asphalt roll of the present invention is significantly superior to the traditional single-material waterproof roll and the improved asphalt roll in terms of fireproofing, waterproofing and self-healing performance. Specifically, the example roll has excellent flame retardant effect, the flame cannot penetrate, and the flame is quickly suppressed, which is much better than the control example. The example roll has no water penetration in the long-term immersion test, while the control example leaks within 24-48 hours. The example roll has a self-healing function and can effectively repair minor scratches, while the control example does not have this function.
[0056] In summary, the flame retardant and waterproof asphalt coil provided by the present invention has good flame retardant properties, can effectively reduce the flame spread speed when a fire occurs, and improve the safety of the building. Moreover, the coil has excellent waterproof performance, can effectively prevent moisture penetration, and ensure the dry environment of the building. The upper surface protective layer prepared by self-healing material can achieve self-healing when microcracks appear on the surface of the coil, thereby extending the service life of the coil. The addition of antioxidants and ultraviolet stabilizers improves the weather resistance of the coil, so that it can still maintain good performance in harsh environments. The provision of a fireproof and heat-insulating layer further improves the flame retardant properties of the coil and reduces the risk of fire. The polytetrafluoroethylene and ethylene-tetrafluoroethylene copolymer of the lower surface protective layer have good chemical stability, can effectively prevent the coil from aging, and improve the service life. The preparation method is simple, the production efficiency is high, and it is convenient for large-scale production.
[0057] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A flame retardant waterproof asphalt roll material, characterized in that: The flame retardant waterproof asphalt membrane comprises the following layers from top to bottom: The upper surface protective layer comprises the following components in parts by weight: 30-35 parts of modified asphalt, 15-20 parts of polyvinyl chloride, 1-2 parts of antioxidant, 0.5-1.0 parts of ultraviolet stabilizer, 3-5 parts of nano-alumina, 2 parts of nano-titanium dioxide, 10-15 parts of magnesium hydroxide and 1-1.5 parts of self-healing material; The waterproof reinforcement layer comprises the following components in parts by weight: 25 parts of modified asphalt, 25 parts of polyvinyl chloride, 12-15 parts of polyester fiber, 2-3 parts of low molecular weight polyethylene, 3-4 parts of toughening agent and 2-3 parts of plasticizer; The fireproof and heat-insulating layer comprises the following components in parts by weight: 35-45 parts of foamed polyurethane, 20-25 parts of expanded perlite, 10-15 parts of glass fiber, 0.5-1 parts of magnesium carbonate and 5-10 parts of hollow glass microspheres; The lower surface protective layer comprises the following components in parts by weight: 30-35 parts of polytetrafluoroethylene, 20-25 parts of ethylene-tetrafluoroethylene copolymer, 8-12 parts of aramid fiber and 5-10 parts of plasticizer; The self-healing material is a microcapsule containing 4-6% by mass of dicyanoacrylate, 3-5% by mass of trimellitic anhydride and 1-2% by mass of diisocyanate.
2. The flame retardant and waterproof asphalt coiled material according to claim 1, characterized in that: The antioxidant comprises 10-15% by volume of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 20-25% of dioctyl thiodipropionate, 10-15% of tris[2,4-di-tert-butylphenyl]phosphite, and the remainder of toluene and impurities; The ultraviolet stabilizer is 0.3-0.7 parts by weight of UV-1164 and 0.2-0.5 parts by weight of UV-360; The particle size of the magnesium hydroxide is 1-2 μm.
3. The flame retardant and waterproof asphalt coiled material according to claim 1, characterized in that: The molecular weight of the low molecular weight polyethylene is 1000-5000; the toughening agent is ethylene-propylene-diene monomer; and the plasticizer is dioctyl phthalate.
4. The flame retardant and waterproof asphalt coiled material according to claim 1, characterized in that: The compression strength of the foamed polyurethane is 0.3-0.5 MPa; the particle size of the expanded perlite is 50-100 μm; the particle size of the hollow glass microsphere is 40-120 μm, and the aramid fiber is poly(p-phenylene terephthalamide) fiber.
5. The flame retardant and waterproof asphalt coiled material according to claim 1, characterized in that: The particle size of the microcapsule is in the range of 50-100 μm.
6. A method for preparing a flame retardant and waterproof asphalt coiled material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Separately preparing an upper surface protective layer, a waterproof reinforcement layer, a fireproof and heat-insulating layer, and a lower surface protective layer; The upper surface protection layer, the waterproof reinforcement layer, the fireproof and heat-insulating layer and the lower surface protection layer are compounded after controlling the temperature, and after the compounding is completed, they are cooled and solidified for 30 minutes.
7. The method for preparing the flame retardant and waterproof asphalt coiled material according to claim 6, characterized in that: The preparation method of the upper surface protective layer is: The modified asphalt and polyvinyl chloride are mixed and stirred at 160-180°C to form a uniform molten mixture; Adding antioxidant, UV stabilizer, nano-alumina, nano-titanium dioxide and magnesium hydroxide to the molten mixture in sequence, and continuing to stir until completely uniform; The self-healing material is slowly added in the form of microcapsules, and stirring is continued until the molten mixture is evenly dispersed, and then the molten mixture is coated on the surface of the waterproof reinforcement layer to form an upper surface protective layer.
8. The method for preparing the flame retardant and waterproof asphalt coiled material according to claim 6, characterized in that: The preparation method of the fireproof and heat-insulating layer is as follows: Premixing the foamed polyurethane and the expanded perlite at 60-80°C for 30-45 minutes to form a mixture; Adding the surface-treated glass fibers and hollow glass microspheres into the mixture in sequence, and continuing to mix until uniform; The mixture is heat-pressed at 100-120° C. to form a fireproof and heat-insulating layer.
9. The method for preparing the flame retardant and waterproof asphalt coiled material according to claim 6, characterized in that: The preparation method of the lower surface protective layer is: The polytetrafluoroethylene and ethylene-tetrafluoroethylene copolymer are melt-mixed at 200-220° C. and homogenized by high-speed shear stirring to obtain a homogenized mixture; Evenly adding aramid fibers in a certain proportion into the homogenized mixture, and continuing stirring; After the homogenized mixture is cooled to room temperature, a plasticizer is added, and a degassing treatment is performed under vacuum conditions, and then the mixture is coated on the lower surface of the fireproof and heat-insulating layer to form a lower surface protective layer; The preparation method of the waterproof reinforcement layer is: The modified asphalt and polyvinyl chloride are melted and mixed at 150-180°C and homogenized by high-speed shear stirring; Gradually add low molecular weight polyethylene, toughening agent and plasticizer, and continue stirring until uniform; evenly disperse polyester fiber into the homogenized mixture according to proportion, and continue stirring; The mixture is extruded and cooled to form a waterproof reinforcement layer.
10. The method for preparing the flame retardant and waterproof asphalt coiled material according to claim 6, characterized in that: After coating, the upper surface protective layer is cured for 40 minutes at 70-90°C, the waterproof reinforcement layer is cured for 50 minutes at above 50°C, the fireproof and heat-insulating layer is hot-pressed at 100°C and then cooled to 20°C, and cured for 90 minutes at 20°C, and the lower surface protective layer is cured for 50 minutes at 20°C after coating.
Citation Information
Patent Citations
Wet paved / pre-paved polymer self-adhesive waterproofing rolled material and preparation method thereof
CN102454226A
Modified asphalt mastic and wet-laying waterproof coiled material
CN103614112A
Polyvinyl chloride modified asphalt waterproof roll and preparation method thereof
CN104672927A
Lignin composite polyamide self-healing material and preparation method thereof
CN111732807A
High-performance fully-regenerated polymer modified asphalt waterproof coiled material with self-healing function and preparation method thereof
CN116494609A
